Existentialism and Individualism: A Study of Its Influence on French Society - Girard, Emma (Journal of Philosophy, Culture and Religion, 2024)
Purpose: The aim of the study was to analyze the existentialism and individualism: a study of its influence on French society. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study revealed that existentialism, led by Sartre and Camus, promoted personal freedom and meaning-seeking in a chaotic world, fostering individualism in French society. This philosophy resonated with post-war France, offering a response to societal upheaval. Across literature, cinema, and politics, existentialism influenced narratives of identity and authenticity, leaving a lasting imprint on French culture. Unique Contribution to Theory, Practice and Policy: Existentialism, individualism & social constructivism may be used to anchor future studies on the existentialism and individualism on French society. Develop educational programs and public awareness campaigns to promote critical reflection and dialogue on existentialist themes such as freedom, authenticity, and responsibility in French society. Advocate for policies that prioritize individual autonomy, self-expression, and self-determination while also fostering social cohesion and collective well-being in French society.